Penyuluhan Hukum tentang Tindak Pidana Korupsi melalui Radio Maria Indonesia - Japansen Sinaga; Rolib Sitorus; Joy Zaman Felix Saragih; Ricky Banke (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Legal counselling is one of the effective methods to increase public legal awareness. Legal counselling through mass media, especially radio, is one of the strategic means to reach a wide audience. The legal education activity on corruption crimes held through Radio Maria Indonesia is part of a community service programme conducted by lecturers of the Law Study Programmes of Universitas Pelita Harapan (UPH) Medan Campus. This activity aims to provide a deep understanding to the public about the definition, form, and impact of corruption, as well as the steps to prevent it. Through a communicative approach and easy-to-understand language, this programme is expected to build collective awareness and encourage active participation of the community in supporting corruption eradication efforts. This study analyses the effectiveness of legal education through radio in shaping critical attitudes and more proactive public behaviour towards corruption issues. The results show that radio can be an efficient legal education tool, especially in areas with limited access to formal education or digital technology.